Analyzing Communication and Satisfaction in Mental Health Online Consults for Students - Mirawati, Ira; Wirakusumah, Teddy Kurnia; Rahmawan, Detta (ETTISAL : Journal of Communication, 2023)
Online mental health consultation applications have become increasingly prevalent in Indonesia. Teenagers, including college students use these applications to communicate their problems and seek solutions. This study aims to describe final year students' experiences in using these applications. This study evaluates the effectiveness of an online mental health consultation service through the perceptions of 118 users, utilizing a Likert scale across three key dimensions: usefulness, usability, also integration and infrastructure. The findings indicate a generally positive reception of the service.  In the usefulness dimension, the service scored well in terms of meeting advertised expectations, maintaining consistent quality, fostering optimism, providing clarity on mental health issues, and making users feel at ease. The usability dimension highlighted the enjoyable nature of the application and its benefits, though it revealed a need for improvement in accessibility for users with disabilities. The integration and infrastructure dimension reflected positively on the service's intuitive design and user-friendliness, with high scores in data confidentiality, responsiveness of counsellors, clarity of communication, and effectiveness in addressing user issues. Users also expressed a willingness to reuse the service for future mental health needs, indicating its perceived value and reliability.